Foreign Language Teachers’ Language Proficiency and Their Language Teaching Practice - Richards, H; Conway, C; Roskvist, A; Harvey, S (Taylor & Francis, 2013)
Teachers’ subject knowledge is recognised as an essential component of effective teaching. In the foreign language context, teachers’ subject knowledge includes language proficiency. In New Zealand high schools, foreign languages (e.g. Chinese, French, German, Japanese and Spanish) have recently been offered to learners earlier in their schooling, prompting a demand for more foreign language teachers. A nationwide professional development programme for language teachers is building language teacher capacity to meet the demand. Participants on the programme have a range of language teaching subject knowledge. While some have extensive knowledge of their target teaching language but lack formal language teaching qualifications, others are generalist teachers with an interest in teaching a foreign language who are just beginning to develop their subject knowledge. This paper considers teachers’ subject knowledge, that is, their language proficiency. We report on the differences in the classroom practice of teachers with limited subject knowledge, compared with teachers with more extensive subject knowledge. The data were analysed against key aspects of teaching based on the work of Farrell and Richards. The analysis revealed a variance in the number of key aspects the teachers could manage and differences in their level of effectiveness in managing the key aspects. We highlight the importance for teachers with limited levels of target language proficiency of continuing to develop their subject knowledge in order to maximise the language-learning experience for their students.
Keywords: Subject knowledge; Teacher language proficiency; Foreign language; Modern language; Classroom practice